A Smart Naked-eye Detection for Fe(III) using Ethanol Extract of Purple Sweet Potato - Samanman, Saluma; Daengrot, Charuwan; Hilae, Aslan; Ma, Sureeluk; Sayoh, Ibrahim; Masaesai, Irfan; Sanitt, Poohrawind; Binhayeeding, Narisa; Noitubtim, Madeena; Yakob, Hafeena; Duerasingmamong, Sofia (Asian Health, Science and Technology Reports, 2023)
Simple naked-eye detection of Fe(III) in a water sample by using crude anthocyanin extracted from purple sweet potatoes as a chelating agent was investigated in terms of both qualitative and quantitative detections. Anthocyanin was extracted in ethanol from a purple sweet potato which is a local plant in Thailand. The selectivity of this method for detecting Fe(III) was examined by testing with different metal ions and by regulating the pH of the buffer solution varying from buffer pH 1-12. It was found that Fe(III) responded with a color change at buffer pH 4-11. However, the disodium hydrogen phosphate/sodium hydroxide buffer pH 11 was chosen because it showed no color change from others interference metals. The detection procedure was to add 100 µL of buffer pH 11 and 40 µL of Fe(III) solutions (0.5–100 ppm) to 20 µL of ethanol extract of purple sweet potato solution. The qualitative detection was by observing the color change from light green to brown by the naked eye whereas the quantitative detection was measured by UV-Vis spectrophotometer. The results obtained from naked-eye detection were evaluated by comparing them with the detection results from the UV-Vis spectrophotometer. Our results show that crude anthocyanin used as a natural chelating agent could be employed for semiquantitative determination by naked-eye detection of 3 color shades depending on Fe(III) concentrations. Importantly, this work could be potentially applied to real water samples as a simple, rapid, low-cost, highly accurate and environmentally safe procedure.